Left Kidney Undifferentiated Spindle Cell Sarcoma with Myeloid Cell Leukemia-1 Amplification: Therapeutic Response to Bortezomib, Venetoclax, and Dexamethasone Therapy - Cheng-Yu Tang; Chueh-Chuan Yen (Journal of Cancer Research and Practice)
The overexpression of myeloid cell leukemia-1 (MCL-1) has been identified in numerous hematologic malignancies and solid tumors. Currently, there are no selective MCL-1 inhibitors. Here, we present a case of left kidney undifferentiated spindle cell sarcoma with MCL-1 amplification. The tumor showed primary resistance to chemotherapy and immune checkpoint inhibitors. Combination therapy of bortezomib, venetoclax, and dexamethasone demonstrated a positive response, resulting in a stable tumor condition for 6 months. To our knowledge, this is the first report to mention the clinical efficacy of bortezomib, venetoclax, and dexamethasone therapy in an MCL-1-amplified solid tumor.